Familial hypercholesterolemia in a rhesus monkey pedigree: molecular basis of low density lipoprotein receptor deficiency. - Hummel, M (1990)
We have recently identified a family of rhesus monkeys with members exhibiting a spontaneous hypercholesterolemia associated with a low density lipoprotein receptor (LDLR) deficiency. By using the polymerase chain reaction, we now show that the affected monkeys are heterozygous for a nonsense mutation in exon 6 of the LDLR gene. This mutation changes the sequence of the codon for amino acid 284 (tryptophan) from TGG to TAG, thereby generating a nonsense codon potentially resulting in a truncated 283-amino acid protein, which needs documentation, however. This G----A mutation also creates a site for the restriction endonuclease Spe I. Using this site as a marker for this nonsense mutation, we have shown that the mutation is present in all of the affected members of the pedigree and absent in unaffected members and that the mutation segregates with the phenotype of spontaneous hypercholesterolemia through three generations. Quantitative analyses of RNA obtained from liver biopsies show that the abundance of the LDLR RNA is also reduced by about 50%. Thus, we have identified a primate model for human familial hypercholesterolemia which will be useful for studying the relationship between the LDLR and lipoprotein metabolism and for assessing the efficacy of diets and drugs in the treatment of human familial hypercholesterolemia.